To study the morbidity and mortality pattern of outborn neonates admitted in neonatal intensive care unit of Indore - Malpani, Preeti; Biswas, Manju; Uikey, Ravi Shankar (Indian Journal of Child Health, 2018)
Introduction: About 50% of infant deaths occur within the 1st month (neonatal period) of life; of these, more than half die during the first 24–48 h after birth. Despite various advances in the newborn care, the neonatal mortality and morbidity remain high, especially, in the developing countries. Objective: The objective of this study is to analyze the factors and the patterns associated with the morbidity and mortality of the newborns. Materials and Methods: This retro pective study was conducted from August 2014 to September 2016. Medical records of 500 outborn neonates admitted in the neonatal intensive care unit of a medical college of Central India were reviewed. The morbidity and mortality pattern of neonate was studied and correlated with birth weight, gestational age, sex, chief complaint, and the underlying cause. Results: There was male preponderance in the study group (60.2%) and male-tofemale ratio was 1.5:1 (p<0.05); preterm babies accounted for 48.6% and term babies 51.40% of neonatal death. The outcome of hospitalized newborn showed that 62% of the newborns were discharged, 28.4% newborn expired, and 9% newborn left against medical advice. Respiratory distress syndrome (RDS) (46.4%) was the leading cause of death, followed by neonatal sepsis (21.9%) and prematurity (15.49%) Conclusion: The major causes of neonatal death were found to be RDS, neonatal sepsis, prematurity, low birth weight, and birth asphyxia. Hence, it is the need of the hour to improve the health of the mother, to give birth to healthy babies.